Training Translators in China - Xu, Jianzhong (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractTranslation training in China has a long history, but it is only in the last two decades that translation training has been developing increasingly fast. This article firstly reviews the history of translation training in China, then examines its present practice such as training program, training materials, training methods, interpretation training, advanced translation training, and Translator Accreditation Tests, and finally makes suggestions for improvement of training translators in China.